KEUNIKAN DAN KESEHARIAN ANAK AUTISME DI SKHN 02 KOTA SERANG - Silfy Maulidiyah; Yahdinil Firda Nadhirah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research was conducted to recognize and understand the uniqueness and daily life of children with special needs (ABK) which focuses on children who have a type of disorder with the brain's nerves or what we often call "autisme". This research is important because it is related to the brain's nerves. which greatly influences a person's behavioral patterns and their sense of social interaction as well as delays in communicating or talking to other individuals.This research uses a qualitative approach to writing. In this research the author describes written words both orally and in writing which comes from interviews with teachers at the school and even with the students concerned. The author also took data in the research. this is through direct observation and through documentation. In this research, it is hoped that we will be able to find out and recognize the uniqueness and daily life of children with autism